CONVERGENCE OF EDUCATION IN THE QUR'AN AND ITS IMPLICATIONS FOR EARLY CHILDHOOD EDUCATION - Hikmah, Nurul (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The initiator of the convergence theory is Leouis William Stern. He is a Germany Psychologist and philosopher. Purpose: This research aims to determine the convergence of education in the Qur'an and its implications in early childhood education. Method: This research uses qualitative research using Maudhu'i interpretation. Result: In this research, it can be understood that educational convergence in the Qur'an carries a theocentric educational paradigm. Theocentric convergence education necessitates the integration of Fitrah and the environment based on Tawhid. Fitrah is not only limited to cognitive ability, even heredity alone, but is broader than that. Fitrah includes munazalah fitrah and nasabiyah fitrah (heredity). Likewise, the environment includes both divine and makhluqiyah. Conclusion: The implications of educational convergence in the Qur'an on early childhood education can be seen in the principles of early childhood education which include; PAUD is oriented towards the child's nature, PAUD is designed based on developmental phases, PAUD is oriented to the child's level of thinking, and the child's knowledge is actively built, the Al-Qur'an and kauniyah verses become learning sources and institutional designs that seek to integrate school and family.